A Survey on the Prevalence of Thyroid Disorder Induced by Demography and Food Habits in South Indian Population - N.J, Nimmy; P.M, Aneesh; M.P, Narmadha; R.H, Udupi; K.M, Binu (Indian Journal of Pharmacy Practice)
Introduction: Thyroid disorders are among the most common endocrine disorders in India. The prevalence and pattern of the thyroid disorders depends on age, sex, geographical factors, food habits and on iodine intake. Aim and Objective: To assess the prevalence and role of geographical factors, family history, medical history, menstrual history and food habits in the incidence of thyroid disorders. Materials and methods: 1000 responders from 4 different geographical areas were interviewed using a pre-designed proforma, demographic details, family history, food habits and suspecting symptoms of the responders were collected. Results: Food habits plays an important role in the fluctuation of thyroid hormone. The distribution of the thyroid patients were found to be more in Coastal area(%) where as Non coastal , Mid-land, Hilly area have low prevalence of thyroid disorder. Conclusion: The factors associated with the prevalence are mainly food habits especially the intake of sea food, coconut, tapioca. It was also found that geographical feature of the area plays an important role in inducing the disorder.It was observed that anything too much can induce fluctuation in thyroid hormones.
Keywords: Hypothyroidism; Thyroxin; Menstrual history; Thyroidism